Empathy differences by gender and specialty preference in medical students: a study in Brazil - Santos, Mariana A. (Int J Med Educ, 2016)
OBJECTIVES: We have conducted this study to assess medical students’ empathy and to examine empathy differences by students’ socio-demographic characteristics, including gender, and specialty preference. METHODS: We have conducted a cross-sectional and descriptive research. Among 595 medical students registered at the Federal University of Santa Catarina (Brazil) in 2012, we have selected a sample of 320 enrolled in the first, third, fifth, seventh, ninth, eleventh, and in the last semester of the course. The response rate obtained was 70.6% (n=226). Data was collected by using a self-report questionnaire, and the variables analyzed included course semester, socio-demographic characteristics (such as age, gender, household monthly income and parents level of education), students’ specialty preference, and empathy assessed by the Jefferson Scale of Empathy. We have used descriptive statistics, 95% Confidence Interval for percentages, Student's t-test, and Analysis of Variance to analyze the data. RESULTS: Mean empathy among students was (M=119.7, SD=9.9), with no difference by according to semester (F((6,219))=1.5, p=.2). Empathy means were higher among females (M=118.3, SD=10.6) than among males (M=121.0, SD=9.3, t((222))=-2.1, p=.032). Students who preferred a people-oriented specialty obtained significantly higher mean scores (M=121.5, SD=8.1) in comparison to students who preferred technology-oriented specialties (M=118.0, SD=11.3, t((135))=2.4, p=.02). CONCLUSIONS: Our study has found consistently high scores of empathy among medical students enrolled in all levels of training at the Federal University of Santa Catarina, and higher empathy among women and students who intend to pursue a people-oriented specialty. Conclusions on higher empathy among medical students require further study.